GREEN BUILDING IN POST-WAR RECONSTRUCTION: ANALYSIS AND DEVELOPMENT OF RECOMMENDATIONS - Журавська, Наталія; Авдикович, Яна (SWorldJournal, 2023)
«Green construction» is an approach to the design, construction and operation of buildings that aims to reduce the negative impact on the environment. One of the key aspects of green construction is the efficient use of resources: the use of energy-effici